PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL MODERASI (Studi Pada Perusahaan Perdagangan Ritel MakananYang Terdaftar di Bursa Efek Indonesia Periode 2019-2021) - Suciati, Laras; Hambani, Susy; Warizal, Warizal (Komunitas Manajemen Kompetitif, 2024)
This study aiims to determine the effect of profitaibility aind compainy size to eairnings mainaigement with finainciail distress ais ai moderaiting vairiaible in food retaiil traiding compainies listed on the Indonesiai Stock Exchainge during the 2019-2021 period. This type of reseaiirch is descriptive reseaiirch with quaiintitaiitive aiipproaiich. The results showed thaiit profitaiibility aiiffects on eaiirnings maiinaiigement. The size of the compaiiny haiis no effect on eaiirnings maiinaiigement. Then the results of moderaiition regression testing showed thaiit finaiinciaiil distress aiis aii moderaiition vaiiriaiible in this study showed thaiit it could not moderaiite the effect of profitaiibility on eaiirnings maiinaiigement. Finaiinciaiil distress vaiiriaiibles thaiit moderaiite firm size with eaiirnings maiinaiigement show thaiit finaiinciaiil distress caiin aiict aiis aii moderaiitor thaiit strengthens the interaiiction between firm size aiind eaiirnings maiinaiigement.